Pengaruh Promosi Media Tiktok dan Kualitas Produk Terhadap Loyalitas Pelanggan pada UMKM Fashion (Study Kasus Toko Furiex Kec. Cihampelas Kab. Bandung Barat) - Nizar Nursamsi; Umi Narimawati (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study was motivated by the low level of customer loyalty at Furiex Store, a fashion micro, small, and medium enterprise (MSME) located in Cihampelas District, West Bandung Regency. Although Furiex Store has utilized TikTok as a promotional platform and gained considerable online popularity, this has not been sufficient to enhance customer loyalty. This study employed a quantitative approach using descriptive and verificative research methods. The descriptive analysis revealed that the TikTok Social Media Promotion variable obtained an average percentage score of 67.3%, Product Quality 65.1%, and Customer Loyalty 64.8%, all of which were classified as strong. The partial hypothesis test indicated that TikTok Social Media Promotion had a positive and significant effect on Customer Loyalty (t = 6.383; p < .001). Similarly, Product Quality had a positive and significant effect on Customer Loyalty (t = 3.577; p = .001). The simultaneous hypothesis test demonstrated that TikTok Social Media Promotion and Product Quality jointly had a positive and significant effect on Customer Loyalty (F = 35.198; p < .001). The coefficient of determination (R²) of 0.431 indicates that the two independent variables explained 43.1% of the variance in Customer Loyalty, while the remaining 56.9% was influenced by other factors not examined in this study. Furthermore, TikTok Social Media Promotion was identified as the most dominant factor influencing Customer Loyalty, with a standardized beta coefficient of 0.518, compared with Product Quality, which had a beta coefficient of 0.290.